Kombinasi Swedish Massage dan Aromaterapi Lemon untuk Menurunkan Nyeri Post Sectio Caesarea: Combination of Swedish Massage and Lemon Aromatherapy to Reduce Post Sectio Caesarea Pain - Dafrosia Darmi Manggasa (Jurnal Bidan Cerdas, 2021)
Introduction: Artificial delivery with the Sectio Caesarea (SC) procedure can cause pain in the patient. Pain that is left untreated can have a negative impact on both the mother and the baby. Pain management can also use massage or aromatherapy interventions that provide a relaxing effect. This study aims to assess the effectiveness of combined therapy Swedish massage and lemon aromatherapy in reducing post-SC pain. Methods: Quasi-experimental design with two groups pre-post test. This study was conducted at Poso Regional Hospital from October to December 2019. The sample was 32 post-SC patients who experienced pain who were taken using the purposive sampling technique. Swedish massage intervention was carried out 4 times. The pain was measured before intervention and after intervention using the Numeric Rating Scale. Data analysis used the Wilcoxon and Mann-Whitney tests. Results: This study showed that the intervention group with combined therapy Swedish massage and lemon aromatherapy showed a significant reduction in pain scores with a mean after the intervention of 3.19 and in the control group with Swedish massage only the mean value was 3.88, statistical analysis obtained p-value 0.031. Conclusion: The combined therapy Swedish massage and lemon aromatherapy is effective in reducing the pain score of post-SC patients, so it is suggested to be one of the nursing interventions to reduce post-SC pain